Lesser prairie-chicken demography, resource selection, and habitat response following megafire in the mixed-grass prairie - Parker, Nicholas James (Kansas State University, 2021)
Fire is an ecological driver that historically interacted with grazing and periodic drought throughout large portions of the Great Plains to maintain grasslands used by several wildlife species. More recently, fire suppression, coupled with changing climate and landscapes, has led to altered grassland ecosystems that may be more likely to experience massive wildfire events known as megafires. Megafires (>40,000 ha) have extreme socioeconomic impacts and may also affect grassland-dependent wildlife including lesser prairie-chickens (Tympanuchus pallidicintus). The lesser prairie-chicken is a grouse species of the southern Great Plains that has experienced population declines since the 1980s, primarily as a result of grassland habitat degradation and loss. While fire has long functioned as an ecological driver to shape grassland habitat, knowledge about the influence of megafires on lesser prairie-chickens and their habitat is lacking. To better understand how remaining grasslands and lesser prairie-chickens may be impacted by megafire, I hierarchically evaluated lesser prairie-chicken survival, reproduction, resource selection, and habitat response to a 2017 megafire at a site inhabited by lesser prairie-chickens in the mixed-grass prairie of Kansas, USA (Starbuck fire, ~254,000 ha). I captured lesser prairie-chickens on leks during the spring before (2014–2015) and after (2018–2019) the fire, attached VHF radio and GPS satellite transmitters, and tracked individuals to evaluate survival, reproduction, and habitat selection. To estimate population trends, I conducted counts of male attendance on leks before and after the fire. There was a 67% decline in the number of attending males on leks post-fire and a 46% decline in the number of occupied leks post-fire. Despite the population decline indicated by lek counts, female breeding season adult survival remained similar before (0.63 ± 0.08) and after the fire (0.64 ± 0.08), as did chick survival (before: 0.27 ± 0.03; after: 0.32 ± 0.11), while nest survival trended lower post-fire (before: 0.42 ± 0.06; after: 0.27 ± 0.07). Individual space use was evaluated using 95% isopleth Brownian Bridge home ranges, and did not differ before (828 ± 110 ha) and after (719 ± 101 ha) the fire. However, home ranges included 5 times more percent cover of Conservation Reserve Program (CRP) fields after the fire compared to before, suggesting CRP/cropland landscapes with disjointed fire fuel availability can provide refugia during extreme events. An analysis of lek attendance corroborated home range results, with greatest male lek attendance in areas with more surrounding cropland post-fire, opposite of trends seen before the fire and lesser prairie-chicken literature. Step selection revealed lesser prairie-chickens strongly avoided wooded areas before and after the fire, indicating that although I did see mortality of woody species, burned woodlands did not become available for use by lesser prairie-chickens. Furthermore, lesser prairie-chickens avoided burned areas post-fire, suggesting limited habitat availability up to 3 years post-fire and emigration from the study site. My analysis of fine-scale habitat and grassland vegetation characteristics response supported a decrease in available cover, with a 32% decrease in 100% visual obstruction, 17% decrease in litter depth, and a 16% increase in bare ground. Based on vegetation criteria, abundance of nest habitat decreased 34% one year post-fire; however, nest habitat and many vegetation characteristics returned to pre-fire levels within two years post-fire, thanks in part to substantial growing season precipitation received in the years following the fire (>70 cm/year). The large size and intense nature of the fire affected lek attendance, habitat abundance, and nest survival, but had no lasting (>2 year) detrimental impacts for grasslands or lesser prairie-chicken habitat. Post-fire recovery of grasslands did not correspond with a rebounding population and it will likely take >3 years for lesser prairie-chickens to fully recolonize burned grasslands. My results indicate that multiple management strategies (e.g., CRP enrollment, post-fire removal of snags, prescribed fire) are needed to manage lesser prairie-chicken habitat and limit future megafires.
Keywords: Lesser prairie-chicken; Megafire; Mixed-grass prairie; Demography; Resource selection; Wildfire